Teamwork in organizations: three interventions - Solf Zárate, Arturo (2021)
Three interventions are presented to promote teamwork in organizations: Team Development, Team Building, and Team Training. This study is motivated by the need to specify the differencesbetween these interventions. It is aimed mainly at Psychology students. The document includes essential aspects from a practical perspective and intends to encourage students to continue learning on the subject, which is currently experiencing extraordinary development.